EFFECT OF SUGARCANE BY-PRODUCT BASED COMPLETE RATIONS ON GROWTH AND CARCASS CHARACTERISTICS IN BUFFALO BULL CALVES - RAGHAVA RAO E, PRASANNA KUMAR R SIVAIAH K (Indian Journal of Animal Production and Management, 2017)
Six rations comprising of five complete rations and one conventional ration (containingchopped hybrid Napier and concentrate mixture) were formulated by using sugarcane byproductsand other crop residues and balanced concentrate mixture in the mash form.These rations were compared by feeding to 24 Murrah buffalo bull calves for a period of 167days using Randomized Block Design to study the effect of processing of complete diet ongrowth, nutrient utilization and carcass characteristics. Highest ADG (610.0g.) recorded inbuffalo bull calves fed on complete ration-II (Sugarcane tops, maize stover and balancedconcentrate mixture) when compared among the complete rations and control. The cost ofcontrol ration per kg live wt.gain was Rs.41.14.The cost of complete ration per kg live weightgain was higher in control than complete rations though insignificantly different. The cost ofcomplete ration per kg live weight gain was reduced by Rs.3.11, 8.69, 8.60, 10.92 and 8.10for complete rations-I, II, III, IV and VI, respectively, when compared to control diet. Thedressing percentage on live weight was significantly (P